The impact of FinTech literacy on digital entrepreneurial intentions: Exploring crowdfunding, blockchain, and AI through a social cognitive career theory lens - Sy Long Pham; Anh Duc Do; Dieu Linh Ha; Trinh Mai Van; Anh Duc Le; Thi Phuong Hien Tran (Entrepreneurial Business and Economics Review (EBER), 2025)
Objective: The objective of the article is to investigate the association between FinTech literacy and the intention to become digital entrepreneurs utilizing the social cognitive career theory (SCCT). Specifically, it sheds light on how three aspects of FinTech literacy (crowdfunding, blockchain, and artificial intelligence) influence individuals' digital entrepreneurial self-efficacy and outcome expectations. Additionally, it examines the separate and sequential mediation roles of digital entrepreneurial self-efficacy and outcome expectations in the connection between literacy in crowdfunding, blockchain, and AI and digital entrepreneurial intention. Research Design & Methods: The conceptual model was analysed using structural equation modelling with the bootstrapping method based on data from a sample of 978 university students in Vietnam. Findings: Our results revealed significant direct impacts of FinTech literacy dimensions on individuals' self-efficacy and outcome expectations regarding digital entrepreneurship. Moreover, the mediation analysis uncovered distinct and sequential mediation roles of self-efficacy and outcome expectations in the correlation between the three components of FinTech literacy and the intention to establish digital start-ups, offering new insights into how crowdfunding, blockchain, and AI literacy drive the intention to launch digital ventures. Implications & Recommendations: This study emphasizes the importance of FinTech literacy for digital entrepreneurship. Academic programs should provide practical FinTech training, and policymakers must support FinTech literacy through policies and resources. Incubators and accelerators can integrate FinTech training to prepare entrepreneurs for the digital economy better. Contribution & Value Added: In this study, we explore the SCCT framework, offering novel theoretical insights into the psychological drivers of digital entrepreneurship. The study significantly advances the field by highlighting the importance of FinTech literacy and sets a new agenda for future research. These findings expand our theoretical understanding and provide actionable recommendations for educational institutions, policymakers, and the entrepreneurial ecosystem.
Keywords: L26; M13; 330; digital entrepreneurial intention; FinTech literacy; crowdfunding; blockchain; artificial intelligence